Resistance in pearl millet against rust - and K.S. AULAKH, P.P.S. PANNU, S.S. SOKHI (Indian Phytopathology, 2002)
Studies conducted under field conditions in Hyderabad, India, revealed high levels of resistance in 4 entries of Pennisetum glaucum, (852B, ICMB-87001, DIC-14-P23 and PMIN 86-1) against rust (Puccinia substriata var. indica). Fifteen entries showedslow rusting behaviour. The resistance against rust was found under the control of a single dominant gene in the entries, 7042-1-4-4 and IP 8695-4 whereas in the entry 700481-27-5-2, the resistance was found to be governed by 2 genes (1 dominant, 1 recessive). Similarly, the segregation pattern in the F2 of the cross 7042-1-4-4X700481-27-5-2 showed duplicatory gene action of the 2 different genes.